(untitled) (Revista de História Regional, 2026)
The economic integration of Spanish immigrants into the Oriente province represents a phenomenon of notable complexity, particularly visible in the mining sector. Far from being limited to a marginal role, these actors, during the period from 1880 to 1933, developed business strategies that enabled them not only to integrate into but also to lead the exploitation of the region’s mineral resources. This paper aims to identify the tactics employed by Hispanic immigrants to penetrate the economic framework of the regional mining industry. The analysis of available records from mining claims, notarial protocols, and mercantile society registries from the Historical Archive of Santiago de Cuba and the Historical Archive of Holguín reveals three main, intertwined mechanisms that explain their success: productive diversification, the formation of strategic alliances, and the intensive use of legal instruments such as power of attorney. The development of these sophisticated strategies was a response to a high-risk environment that rewarded prudence, diversification, and partnership. The article argues that these practices were not merely methods for maximizing profits, but essential safeguarding mechanisms that allowed a segment of the Spanish community to prosper and transform mineral wealth into a fundamental pillar for regional economic development during this period.